Pinelliae Rhizoma Praeparatum Cum Alumine Extract: Sedative and Hypnotic Effects in Mice and Component Compounds. (28th April 2019) - Lin, Sisi; Nie, Bo; Song, Ke; Ye, Ren; Yuan, Zhengzhong
Abstract : Pinelliae Rhizoma Praeparatum Cum Alumine (PRPCA) is useful for eliminating dampness and phlegm in clinical settings, targeting the main mechanisms of insomnia as defined in traditional Chinese medicine. However, little is known regarding the sedative and hypnotic effects of PRPCA. In the present study, we examined the sedative effects of PRPCA via a locomotor activity test and aimed to determine the most appropriate concentration of PRPCA for achieving these effects. The strongest sedative effects were observed at a PRPCA concentration of 0.45 g/ml. In addition, we investigated the hypnotic effects of PRPCA and its role in promoting sleep via sleep monitoring and vigilance state analysis. PRPCA increased rapid eye movement (REM) sleep and non-REM (NREM) sleep while decreasing wakefulness. In addition, PRPCA decreased the number of bouts of wakefulness (16–32 s and 32–64 s) and increased the number of bouts of NREM sleep (128–256 s). Furthermore, we identified a total of 32 component compounds via chromatography and mass spectrometry. Hence, the current work provides valuable information regarding the sedative and hypnotic effects of PRPCA and its regulatory mechanisms in promoting sleep.